Ukraine : System of Financial Oversight and Governance of State-Owned Enterprises - World Bank (Washington, DC, 2013)
The report focuses on the system of financial oversight and governance of state-owned enterprises in Ukraine. State-owned enterprises (SOEs) continue to represent a significant share of Ukraine's economy, and play a dominant role in sectors such as rail, transport, utilities, energy and telecommunications. These enterprises play an important role for the government by remitting dividend payments to the national treasury to fund the country's development agenda. At the same time, these same enterprises government receive fiscal support through a transfer of budgetary resources, issuance of guarantees for enterprise debt, facilitation to lines of credit, and other financial instruments. Ukraine's SOE sector has a wide range of ownership and management schemes. The basic legal framework for SOE oversight, defined in the Commercial Code of Ukraine, provides for the delegation of responsibilities across several ministries/agencies. As a result, there are overlapping roles across different government institutions, and gaps with regard to active monitoring and oversight. In practice, the SOE oversight function of the line ministries is primarily exercised through a review of the reports submitted by the SOEs on the implementation of financial plans. However, the review is typically light, and its efficiency is undermined by the limited clarity of the operating objectives for SOEs, and limited usefulness of the performance management framework. Moreover, the underlying data used to measure performance indicators is not validated and its reliability is uncertain. Even though the current performance management framework can be improved, performance evaluations are not conducted for a substantial number of SOEs which seriously undermines the effectiveness of oversight.